Peran Anggaran dan Efektivitasnya Dalam Pengendalian Manajemen Pada UMKM - Kurniawan, Dody (Fibonacci: Jurnal Ilmu Ekonomi, Manajemen dan Keuangan, 2024)
This research examines the role of budgets in increasing the effectiveness of management control in Micro, Small and Medium Enterprises (MSMEs). MSMEs are the backbone of the Indonesian economy, making a significant contribution to Gross Domestic Product (GDP) and employment. However, many MSMEs face challenges in effective budget management. This research uses a library study method by collecting data in the form of books, journals and internet articles related to the topic in this research. This research found that the budgeting process consisting of formulation, adoption, implementation and control is very important in the financial management of MSMEs. Obstacles in budgeting in Indonesia include sectoral budget allocation without careful planning and sub-optimal budget management. An efficient and participatory budgeting process can significantly improve the performance of MSMEs. With good budget management, MSMEs can ensure appropriate resource allocation, reduce risks, and achieve strategic goals. This study confirms the importance of budgeting as an essential management tool for organizational success.